Implementasi Kebijakan Pengelolaan Sumber Mata Air Di Desa Nyatnyono Kabupaten Semarang - Ali Rizqi, Nur Kholish; Susanti, Martien Herna; Sumarno, Sumarno (Unnes Political Science Journal, 2017)
The source of water Nyatnyono are the areas that have the potential is large enough in order to improve the quality of revenue the Nyatnyono village. Perdes No. 2 Tahun 2015 as a product of the village Nyatnyono, to set up the management of the assets of the Nyatnyono village to be neat and have a clear legal basis. Management of the assets of the village Nyatnyono as Perdes No. 2 Tahun 2015 so as not to be misused by certain elements so that it will be useful for the village and surrounding communities in metting of the needs. The formulation of a problem in this study are: 1) how the implementation of policy managements of springs Nyatnyono village as Perdes No. 2 Tahun 2015 of the village assets. 2) the impact of Perdes No. 2 Tahun 2015 to improve the welfare of the Nyatnyono. The study with the qualitative. The research in the Nyatnyono village the district of semarang. The research  is the implementation of policy and policy impact of the managements of water resources in the Nyatnyono village. The method of collecting data in this study interviewing, documentation and observation. Methods of data analysis in research by using a step 1) data collection 2) the reduction data 3) the presentation of data 4) the withdrawal of the conclusion. The research result showed that: 1) implementation Perdes of the managements village assets. village chiefs as a full management assets of the Nyatnyono village, and human resources in the management of the necessary supervision. 2) a positive impact in terms of the management of water located in the Nyatnyono village is traders around spring Kalimah Toyyibah and improvement of access roads Nyatnyono. The negative, lack of control or supervision of human resources in the field, especially the water resulted in the revenue the village used by unscrupulous persons who are not responsible for personal again. Advice: there needs to be given to Perdes No. 2 Tahun 2015 of the village assetsto clarify the implementation of the management asset as well the rural need for awareness of the government and society on the management of water resources in the Nyatnyono village to in policy process because conflict and the impact of the policy can benefit the Nyatnyono village. 2) socialization between the government of the village by society about implementation of Perdes. In addition the government Nyatnyono village in the implementation of the policy should also be maximal in terms of supervision agency execution in the field.